Optical and spin properties of localized and free excitons in GaBixAs1−x/GaAs multiple quantum wells. (4th August 2016) - Balanta, M A G; Kopaczek, J; Orsi Gordo, V; Santos, B H B; Rodrigues, A D; Galeti, H V A; Richards, R D; Bastiman, F; David, J P R; Kudrawiec, R; Galvão Gobato, Y
Abstract: Raman spectroscopy and magneto-photoluminescence measurements under high magnetic fields were used to investigate the optical and spin properties of GaBiAs/GaAs multiple quantum wells (MQWs). An anomalous negative diamagnetic energy shift was observed at higher temperatures and higher laser intensities, which was associated to a sign inversion of hole effective mass in these structures. In addition, an enhancement of the polarization degree with decreasing of laser intensity was observed (experimental condition where the emission is dominated by localized excitons). This effect was explained by changes of spin relaxation and exciton recombination times due to exciton localization by disorder.